SPATIAL ASSOCIATIONS AND SPECIES DIVERSITY OF TROPICAL BROADLEAVED FOREST, GIALAI PROVINCE - Hong Hai, Nguyen; Thi Thu Hien, Cao (Journal of Forestry Science and Technology, 2019)
Spatial association and species diversity of species-rich tropical forests can be characterized by their spatial patterns. We applied the quantitative analyses based on relationships of spatial distribution of tree species. In a 2-ha plot of a tropical broadleaved forest stand in Kon Ha Nung, Gia Lai province, all tree individuals with DBH ≥ 2.5 cm were mapped and their characteristics (i.e., DBH and species) were recorded. We applied two different types of analyses: (1) Overall inter-specific associations through a classification scheme based on bivariate nearest neighbor distribution function D12(r) and Ripley’s K function K12(r), (2) Individual species Area Relationship. The findings showed that: (1) In total of 506 species pairs analyzed up to spatial scales of 50 m, the most frequent association type was mixing of all species pairs (38.9%). Segregation and no association types between species were observed with 27.1% and 25.9%, respectively. The least frequent type was partial overlap (8.1%). (2) Among 23 dominant species, 13 species (56%) were regarded to diversity accumulators, three species (13%) were diversity repellers and seven species (31%) were neutral at different scales up to 50 m. We found significant evidences of the main ecological theories such as dispersal limitation, Neutral theory and other effects including the stochastic dilution and species herd protection. We suggest using both the bivariate nearest neighbor distribution function and the individual species area relationship as advantageous approaches in forest ecology study.